3d + 8 = 2d - 7
3d -2d = -8 - 7
1d = - 15
d = -15
Chat with our AI personalities
5d+3d = 15 8d = 15 d = 15/8 = 1.875
8d = 5d+18 8d-5d = 18 3d = 18 d = 6
I--2a+b=2c+2d II--2a+b=c+2d III--a+2b=3d * Here if we perform (I)-(II), we get, c=0 * Using the c we can prove b=0 using (I)-(III). * Now replace 'b' & 'c' as 0 in (I), then we get a=d. Email me at yash2008gates@gmail.com for any queries. I will be very thankful to receive your queries.
2(3d+7)=5+5d. 6d+14=5+5d 6d+9=5d 9=-1d d=-9 I think that's correct. If it is, ur welcome.
It is an expression and can be simplified to: 3d+f+1